Introduction to computer security - Goodrich, Michael T.; Tamassia, Roberto, 1960- (Boston : Addison-Wesley, 2011)
Unlike most other computer security textbooks available today, Introduction to Computer Security, 1e does NOT focus on the mathematical and computational foundations of security, and it does not assume an extensive background in computer science. Instead it looks at the systems, technology, management, and policy side of security, and offers students fundamental security concepts and a working knowledge of threats and countermeasures with (3z(Bjust-enough(3y (Bbackground in computer science. The result is a presentation of the material that is accessible to students of all levels.s
1 Introduction -- 2 Physical Security -- 3 Operating Systems Security -- 4 Malware -- 5 Network Security -- 6 Network Security II -- 7 Web Security -- 8 Cryptography -- 9 Security Models and Practice -- 10 Distributed-Applications Security.
Includes bibliographical references (p. 541-546) and index.
1
Keywords: Computer security